Microbiological characteristics and inflammatory cytokines associated with preterm labor - Discacciati, Michelle G.; Simoes, Jose A.; Silva, Marcia Guimarães da [UNESP]; Marconi, Camila [UNESP]; Brolazo, Eliane; Costa, Maria L.; Cecatti, Jose G. (Springer Heidelberg, 2011)
To evaluate vaginal microflora and interleukin-1 beta (IL-beta), interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor-alpha (TNF-alpha) concentrations in the cervicovaginal fluid of a group of pregnant women in preterm labor when compared with a group of full-term pregnant women not yet in labor.Case-control study performed in a University tertiary referral maternity in Campinas, Brazil with 45 pregnant women in preterm labor and 45 full-term pregnant women not in labor. All patients underwent speculum examination for the collection of cervicovaginal fluid. Bacterial vaginosis (BV) was diagnosed according to the criteria of Amsel and Nugent. Culture was performed for group B streptococcus (GBS) and lactobacilli, and hybrid capture assay for screening for chlamydial and gonococcal infection. Cytokine concentrations were measured using ELISA technique. Statistical analysis was performed using chi(2), Fisher's exact, and crude and adjusted odds ratios. Significance level was defined at 5%. The main outcome measures were cervicovaginal cytokines in preterm labor.IL-6 and IL-8 were significantly associated with preterm labor. The changes in vaginal microflora, as well as BV and GBS, were more frequent in women in preterm labor, although BV and GBS showed no statistical significance. The presence of Candida sp., absence of lactobacilli, positive screening for chlamydial and gonococcal infection and the presence of IL-1 beta and TNF-alpha were not associated with preterm labor.IL-6 and IL-8 and the presence of any type of vaginal infection were the factors that were significantly associated with preterm labor.
Keywords: Preterm labor; Cytokines; Interleukins; Bacterial vaginosis